2011
DOI: 10.1111/j.1742-9544.2011.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Clinical Psychology Training by Students at Australian Regional and Urban Universities

Abstract: Training in clinical psychology in Australia has become increasingly popular after coverage for psychological services under national Medicare was introduced. All regional universities in Australia offer clinical psychology training at the master's level, but little is known about how such training at these universities compares with training in larger, urban universities. Here, we report on results of surveys of clinical students and training directors at regional universities across Australia in order to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Students were roughly split in their willingness to undertake rural placements, which is important given government focus on strengthening health care delivery to these regions. This underscores the fact that regional/rural programmes experienced some comparatively more challenging issues to those faced by urban programmes related to training and retaining clinical psychologists (see Helmes & Pachana, 2011 for more in‐depth discussion of regional issues).…”
Section: Discussionmentioning
confidence: 99%
“…Students were roughly split in their willingness to undertake rural placements, which is important given government focus on strengthening health care delivery to these regions. This underscores the fact that regional/rural programmes experienced some comparatively more challenging issues to those faced by urban programmes related to training and retaining clinical psychologists (see Helmes & Pachana, 2011 for more in‐depth discussion of regional issues).…”
Section: Discussionmentioning
confidence: 99%
“…In an early qualitative study, O'Donovan, Dyke, and Bain () found that most students were very satisfied with their training and that the main sources of dissatisfaction were an emphasis by the university on research over practice, academic staff being busier and more stressed due to changes in university conditions, and some difficulties with supervisors. In a more recent Australia‐wide study, Helmes and Pachana () found that students were overall satisfied with the quality of their training but found the workload heavy and that only a small majority of students found they received sufficient clinical practice. Scott, Pachana, and Sofronoff () found that clinical postgraduate students were overall satisfied with their programmes, with problem areas regarding clinical placement including difficulty obtaining sufficient client contact hours, time‐management difficulties, and limited access to supervisors.…”
Section: Student Experiencementioning
confidence: 99%
“…The introduction in 2007 by Medicare of rebates for psychological services (Better Access to Mental Health Care initiative) has led to greatly increased demand for psychologists in the private sector (Grenyer et al, 2010;Littlefield & Giese, 2008). In response to Better Access and other factors, demand has increased for clinical psychology training programmes (Helmes & Pachana, 2011), with an associated rise in numbers of students requiring clinical supervision.…”
Section: Challenges To Practical Training Within the University-basedmentioning
confidence: 99%
“…A systematic review conducted by Sheen, Graj, Pestell, and McGillivray () has demonstrated that psychology students face educational and supervision‐related risk during clinical placement. Educational risk arises from barriers to clinical placement participation including financial difficulties (Bor, Watts, & Parker, ), extended hours (Helmes & Pachana, ), and limited opportunities for direct supervision (Hatcher, Wise, Grus, Mangione, & Emmons, ; Scott, Pachana, & Sofronoff, ). Furthermore, supervision quality can at times be undermined by poor supervisory style or methods of communication (Atkinson & Woods, ; Dodds, ; Gray, Ladany, Walker, & Ancis, ; Nelson & Friedlander, ; Rhinehart, ; Zinkiewicz, ).…”
Section: Introductionmentioning
confidence: 99%